DINAMIKA SOSIALAGAMA DALAM MERESPON TRANSFORMASI BUDAYA PADA MASYARAKAT HINDU DI KABUPATEN TABANAN - Aryanatha, I Nengah (Widya Sandhi, 2019)
This study examines the emergence of dynamic trends in social solidarity in the midst of religious life in Hindu communities in Tabanan Regency. The study was designed in the form of descriptive research with a case study model. The results showed that the dynamics in social solidarity in the midst of religious life in Hindu communities in Tabanan Regency. can not be separated from the implications as an impact that affects the order of religious life internally. These implications, both of which can be observed empirically or still in the form of symptoms that affect the structure of religious social life